Using fuzzy Choquet Integral operator for supplier selection with environmental considerations - Shahryari Nia, Arash; Olfat, Laya; Esmaeili, Ahmad; Rostamzadeh, Reza; Antuchevičienė, Jurgita (Journal of Business Economics and Management, 2016)
The increasing importance of considering environmental issues as a part of the corporate social responsibility, which has environmental and social impacts as well as affects the image and competitiveness of a firm, has encouraged companies to revise their major processes of supply chain management (SCM). Since the performance of a company heavily relies on its suppliers, it is of vital importance to incorporate environmental criteria into supplier selection problem to satisfy both conventional and environmental criteria, which have only been considered by a limited number of studies. Therefore, following a brief review of green supply chain management (GSCM) and sustainable supply chain management (SSCM) concepts and investigation of supplier selection approaches, this study after focuses on a modified Delphi method that has been applied to determine supplier selection criteria. Also, the intuitionistic fuzzy value (IFV) and interval value intuitionistic fuzzy (IVIF) have been utilised for supplier evaluation regarding the subjective nature and uncertainty of judgment. By using the Choquet Integral operator and fuzzy measures, the best supplier has been selected, and the comparison between IFV and IVIF has been made. This methodology has been applied to a manufacturing company to assess the applicability of the proposed methodology. The proposed methodology can be used for real world problems that contain fuzziness or interacting decision criteria. Moreover, due to a high level of expert involvement in the decision-making process, we claimed that the knowledge of experts has been utilised constructively.